The biogeomorphology associated with a keystone plant species in the sub-Antarctic - Haussmann, Natalie Suzette (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Conservation Ecology and Entomology))--University of Stellenbosch, 2011.